Evidence for Cross-Cultural Support for the Underdog: Is the Affiliation Driven by Fairness and Competence Assessments? - Goldschmied, Nadav; Galily, Yair; Keith, Kenneth (Frontiers in Psychology, 2018)
Jesus told his disciples, “Truly I tell you, it is hard for someone who is rich to enter the kingdom of heaven. Again I tell you, it is easier for a camel to go through the eye of a needle than for someone who is rich to enter the kingdom of God.” (Matthew 19:23-24). Ditto for heroes. The current study suggests that ‘humble beginnings’ is also a prerequisite for one to become an adulated entity. Participants from China, Israel, and Japan read of two sports teams with disparate expectations and/or financial resources about to face each other. Support was extended to the lesser one. When the two domains of comparison were contrasted, participants wished the lower resources/ high expectations team to win the game. This finding was interpreted as an impetus to maintain basic fairness based on competency assessments, both fundamental and universal psychological needs, at the root of the choice to support underdogs. In conclusion, we explore how support underdog relates generally to the concept of heroism.